General purpose search and classification algorithms for distributed information access - Siraj, Fadzilah; Wan Ishak, Wan Hussain (2000)
Networks protocol and software such as HTTP, Netscape and Internet Explorer have significantly ease importation and fetching of on-line information sources available on the Internet for the public, personal and organizational access. These information need to be organized so that users can access and search the information in the convenient way. One of the most popular tools for searching and finding information on the Internet is using the search engine. Many search engines have been made available on the Internet, yet users are not able to efficiently explore and find what they want in information overload. Some search engines displayed hundred of results each time the user requests for specific keywords or queries. Users have to visit each URLs even though the page does not suit their requests.Therefore, it is vital to provide efficient and timely Internet search algorithm to ensure the success of distributed services, particularly to facilitate the current and future applications of national information superhighway. Previous and current research on search engines and information retrieval show that Artificial Intelligence technique is one of the recommended solutions in providing the most relevant, timely and efficient search results for the user.This paper proposed a search engine model that incorporated Artificial Intelligence techniques.